The neocolonial logics underpinning the “war on drugs” in the Philippines - Pablo Leandro Ciocchini (Oñati Socio-Legal Series, 2024)
The “war on drugs” in the Philippines has claimed thousands of people lives and has resulted in the detention of hundreds of thousands of drug users. Legal professionals working in criminal courts have adopted a “punitive paternalism” when dealing with these cases that presented plea bargaining, even in cases based on planted evidence, as helping defendants to change their life habits. The article argues that both the “war on drugs” and the “punitive paternalism” are rooted in the neoliberal policies imposed on the Philippines for decades responsible for reproducing gross income inequality and promoting a narrative blaming individuals for their own economic marginalisation. The analysis shows that the deployment of coercive strategies, such as the “war on drugs”, is still dependant on building consent, in the Gramscian sense. The article shows legal professionals’ contribution to the constitution of a hegemonic order in a context of widespread state-sponsored violence.